Dragonflies and damselflies (Insecta: Odonata) of Nagaland, with an addition to the Indian odonate fauna - Shantanu Joshi; Krushnamegh Kunte (Journal of Threatened Taxa, 2014)
We surveyed odonates in the districts of Kohima, Peren and Wokha in the state of Nagaland, northeastern India, during April and May 2012 and May 2013.  We recorded 69 species, including 43 additions to the known odonates of Nagaland, and one addition—Calicnemia erythromelas Selys, 1891—to the Indian odonate fauna. The known odonate fauna of Nagaland now consists of 90 species in 53 genera and 14 families.  We also describe for the first time the female of Coeliccia schmidti, and partially, a heterochromatic form of the female Ischnura mildredae.